2013
DOI: 10.1002/j.0022-0337.2013.77.11.tb05632.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Risk of Musculoskeletal Disorders Among Brazilian Dental Students

Abstract: The aim of this study was to compare the mean scores of perceived risk factors for the development of musculoskeletal disorders in dental students presently pursuing work/study, according to gender, course series, and the presence of pain/discomfort. The participants were 348 students from the undergraduate course in dentistry at a Brazilian public university. The instrument on work-related factors that could contribute to osteomuscular symptoms and part of the Nordic questionnaire were used. The psychometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…All work related risks and their respective preventive strategies should be explained at the undergraduate training stages, so that students can prevent the onset of MSDs by adopting an ergonomic approach in their dental practice ( Garcia, Presoto & Campos, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…All work related risks and their respective preventive strategies should be explained at the undergraduate training stages, so that students can prevent the onset of MSDs by adopting an ergonomic approach in their dental practice ( Garcia, Presoto & Campos, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The practical follow‐up of ergonomic starts during the pre‐clinical activities of the Restorative Dentistry course, when students are still enrolled in the second year of this degree course, a total of 45 h of training. Clinical activities are also carried out during patient care in the Restorative Dentistry course, during the third year of this degree course , a total of 90 h of training. The major emphasis of the discipline of Ergonomics in Dentistry in this Faculty is to conduct streamlined work together with the maintenance of occupational health.…”
Section: Introductionmentioning
confidence: 99%
“…Dental students’ risk of developing musculoskeletal disorders is high . Strategies should therefore be implemented in their academic programmes in an attempt to reduce this risk .…”
Section: Discussionmentioning
confidence: 99%
“…These requirements affect factors involving visualisation and access to the operating field, which is very small, difficult to see, dark and often shadowed . In an attempt to improve visualisation, students tilt their torsos and necks towards the mouth of the dental mannequin and, in doing so, decrease the distance between their eyes and the mannequin's mouth . According to Presoto et al, the students evaluated in their study also reported that the method they found easiest and quickest for accessing the oral cavity was the lifting of the elbows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation